Hospitality sponsorship program: consumer involvement and product awareness / Marhazlina Ab Hadi - Ab Hadi, Marhazlina (2013)
The relevance of this study lays in the search for the relationship between consumers involvement attributes in sponsorship program and product awareness towards the intention to purchase the sponsors product. In spite of all indicators pointing to the need for a clear understanding of the business value of sponsorships, little is known about basic aspects for the consumers involvement in sponsorship program, product awareness and intention to purchase the product. The paper aims to investigate this issue.Using data from selected literature from relevant journals over a wide period of time have been analysed – additional three events in different hospitality organizations categories, have been evaluated by analyzing responses from participants and attendees from the respective events.A quantitative method of structured survey questionnaire was used. Specifically, respondents were asked to indicate their level of agreement or disagreement with a series of statements based on a five-point Likert scale. The questionnaires distributed were then statistically processed using SPSS Statistics 20. The benefits that a hospitality organizations may obtain by joining a sponsorship program are discussed. This study findings has clearly revealed that consumer involvement activity plays a vital role towards the awareness of sponsor’s product and in consumer purchase intention behaviour. For event managers information and conclusions relevant to reward consumer involvement are also expounded. This paper helps hospitality organizations to take decisions with regard to creating consumer awareness by reviewing important issues relating to both consumers’ involvement in an event in order to reach the consumers awareness and purchase intention towards the sponsor’s product.